A Feminist Reconstruction of the Doctrine of Sin: A Sociology of Religion Perspective - Aliyu, Titus; Ichaba, Amos Ameh (NIU Journal of Humanities, 2026)
The doctrine of sin occupies a central place in Christian theology, yet its historical formulations have often been shaped by androcentric assumptions that obscure or marginalise women’s experiences. This paper undertakes a feminist reconstruction of the doctrine of sin, critically examining how traditional interpretations have perpetuated hierarchical structures and legitimised gender oppression. ​Drawing on feminist theological discourse, hermeneutical strategies, and socio-ethical critique, the study redefines sin not merely as personal moral transgression but as a complex reality manifested in systemic injustice, relational disintegration, and institutionalised violence—particularly against women. By interrogating patriarchal readings of scripture and doctrine, this work demonstrates how feminist perspectives unveil sin as both individual and structural, exposing complicity in sustaining oppressive power dynamics. ​The reconstructed doctrine proposed here affirms the lived realities of women, reorients the understanding of sin towards liberation and justice, and contributes to a more holistic theological anthropology. In doing so, it advances a framework in which resistance to domination and the pursuit of mutuality become integral dimensions of Christian discipleship. This study examines the concept of sin within Christian theology through a feminist lens, challenging traditional interpretations that have often reinforced patriarchal structures and marginalized women’s experiences. By engaging with classical theologians and feminist scholars, this paper reconstructs sin as both personal and structural, emphasizing injustice, oppression, and broken relationships. The study proposes a liberative understanding of sin that priotizes injustice, equality and the full humanity of all persons. Keywords: Sin, Oppression, Patriarchy, Gender Justice, Christian Theology.